A new genus for an Australian thrips (Thysanoptera, Phlaeothripinae) presumed predatory on a waxy eriococcid (Hemiptera, Coccoidea) - Mound, Laurence A.; Wells, Alice (Zootaxa, 2007)
Callococcithrips gen.n. is erected for the species Rhynchothrips fuscipennis Moulton that lives only among the protective waxy secretions of an eriococcid on Kunzea in south-eastern Australia. Larvae and adults of this thrips move rapidly amongst the sticky wax strands, and their maxillary stylets are unusually long and convoluted. Circumstantial evidence suggests that the thrips is predatory on immature stages of the eriococcid. Also transferred to this genus is Liothrips atratus Moulton, based on a single female from Western Australia.